1997
DOI: 10.1089/thy.1997.7.377
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Mutations in the Gene EncodingThyroid Transcription Factor-1 (TTF-1) in Patients with Thyroid Dysgenesis

Abstract: Thyroid transription factor-1 (TTF-1) is a homeodomain-containing nuclear transcription factor, important in regulation of the thyroid-specific genes thyroglobulin (Tg), thyroperoxidase (TPO), and thyrotropin receptor (TSHR). TTF-1 is an early biochemical marker of thyroid differentiation, essential for thyroid development and maintenance of the thyroid differentiated state. It is possible that mutations in titf1 gene encoding TTF-1 could result in failure of the thyroid gland to develop. Single strand conform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0
4

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(27 citation statements)
references
References 18 publications
3
20
0
4
Order By: Relevance
“…Recent studies have described multiple genetic abnormalities associated with CH. [8][9][10][11][12] In a study of DNA from patients with permanent and transient CH, Moreno et al 12 analyzed mutation in the genes for thyroid oxidase 1 (THOX1) and 2 (THOX2) and found that biallelic inactivating mutations in the THOX2 gene were associated with permanent CH and that monoallelic mutations were associated with transient CH. Sunthornthepvarakul et al 8 described 3 siblings with CH that was associated with mutations in the thyrotropin receptor gene; and after finding a similar case, Biebermann et al 9 concluded that mutation of this gene may be the cause of a substantial number of cases of CH.…”
Section: Genetic Basis For Chmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have described multiple genetic abnormalities associated with CH. [8][9][10][11][12] In a study of DNA from patients with permanent and transient CH, Moreno et al 12 analyzed mutation in the genes for thyroid oxidase 1 (THOX1) and 2 (THOX2) and found that biallelic inactivating mutations in the THOX2 gene were associated with permanent CH and that monoallelic mutations were associated with transient CH. Sunthornthepvarakul et al 8 described 3 siblings with CH that was associated with mutations in the thyrotropin receptor gene; and after finding a similar case, Biebermann et al 9 concluded that mutation of this gene may be the cause of a substantial number of cases of CH.…”
Section: Genetic Basis For Chmentioning
confidence: 99%
“…5,6 We report results of thyroid scintigraphy using 123 I or technetium Tc 99m pertechnetate in 210 infants with CH diagnosed during the 24-year period from 1978 through 2002; these cases include 63 previously reported cases 7 ), which we believe support the clinical value of this imaging procedure, particularly when 123 I is used. Additionally, recent discovery of gene abnormalities in CH and in thyroid embryogenesis 2,[8][9][10][11][12][13][14][15][16] suggests that combining results of 123 I thyroid scintigraphy and results of genetic studies may facilitate characterization of the genetic mechanisms of CH.…”
mentioning
confidence: 99%
“…Авторы пришли к выводу, что NKX2-1-мутации не являются частой причиной врожден-ного гипотиреоза. Тем не менее частота NKX2-1-мутаций может быть выше у пациентов с врожденным гипотире-озом, ассоциированным с неврологической патологией и заболеваниями дыхательных путей [16][17][18][19]. В недавнем европейском исследовании у 2 из 150 детей с врожденным гипотиреозом были обнаружены мутации гена NKX2-1.…”
Section: клиническая характеристика и диагностикаunclassified
“…Os rastreamentos de mutação do TITF1 em populações de pacientes com DT apresentaram resultados negativos (30)(31)(32). Dada a importância fundamental deste gene nas morfogêneses pulmonar e cerebral, observada no modelo animal knockout, presume-se que a mutação inativadora em homozigose seria praticamente incompatível com a sobrevivência no período neonatal.…”
Section: Titf1unclassified